Early labor insertion in Latin America: A perspective from business sector needs - Alejandro Valencia-Arias; Robinsson Cardona-Cano; Jerri López-Sánchez; Natalia Herrera-Giraldo; Jackeline Valencia (Cogent Social Sciences, 2023)
AbstractThis study analyzes the labor needs of companies in the Aburrá Valley, Colombia, and the skills required for recent graduates to enter the labor market successfully. The study aims to provide objective data for improving graduate outcomes. Employing an empirical mixed methods approach, the study administered questionnaires to companies to identify their expectations and needs regarding graduate competencies. Additionally, focus groups were conducted with higher education institutions to understand their perspective on student preparation. The study found that companies prioritize training graduates in soft skills, technology, data analysis, languages, and adaptability. Nonetheless, there is a significant deficit in proficiency regarding adaptation to change, office tool management, information analysis, and organizational trends. Additionally, there is a tendency for companies to overlook the necessity of continuous training for interns, which could bolster their professional skills. The study emphasizes the necessity for universities to revise the skill sets of graduates within their programs and harmonize them with pertinent job requirements. It is suggested that enhanced cooperation between universities and companies can foster early job placements, tackle curriculum concerns, and establish frameworks for fostering employability. Taken together, this study offers a unique and innovative solution for bridging the divide between academia and industry. The implications include heightened potential for employment among recent graduates and an overall economic boost for the Aburrá Valley region.